Studi Etnobotani Tradisi Wiwitan Suku Jawa di Desa Berongkal Kabupaten Malang - Sodiki; Diyah Ayu Widyaningrum; Ismi Nurul Qomariyah; Rina Wijayanti (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Ethnobotany is a science that studies the relationship between humans and plants and their traditional use. One of the ethnobotanical studies is found in the Javanese people in Berongkal Hamlet, which is one of the community groups that still preserves traditional ceremonies, one of which is related to the culture of planting rice. This study aims to study ethnobotany in the wiwitan tradition in Berongkal Village. The research was carried out for 2 months (May - June 2025) in Sidomakmur Hamlet, Berongkal Village, Pagelaran District, Malang Regency. This type of research is exploratory descriptive. The research instrument is a questionnaire used for interviews. The stages of the research include determining informants, interviewing informants, taking plant samples, and identifying plants. Data collection is done by means of observation, interviews and documentation. The data analysis technique is qualitative. The results of the study show that in the Javanese community in Berongkal Village there is a traditional wiwitan ceremony related to the culture of planting rice with one of the activities carried out, namely placing offerings near the rice fields that have been planted with rice. In carrying out the traditional ceremony, as many as 15 types of plants and other media such as mineral water and jugs are used. The part of the plant that is most widely used in the wiwitan tradition is the flower. In addition to the Javanese, several types of plants are also used by other community groups. This indicates the existence of ethnic closeness between these community groups.